Republic of Moldova : Second Reviews Under the Extended Arrangement and Under the Three-Year Arrangement Under the Extended Credit Facility, and Request for Waiver of Applicability of Performance Criteria-Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Moldova. (IMF Staff Country Reports; Country Report, 2011)
Moldova's economy has nearly recovered from the 2009 recession, with GDP growing by almost 7 percent in 2010. GDP rebounded by 6.9 percent in 2010 after declining by 6 percent in 2009. The key objectives for 2011 are to advance fiscal consolidation, keep inflation under control despite adverse shocks, and support balanced growth. The growth momentum is expected to continue in 2011 and beyond, leading to a temporary widening of the current account deficit. The 2011 budget seeks to maintain the pace of fiscal consolidation with emphasis on permanent reduction in current spending.